Motivasi Petani dalam Pengembangan Usahatani Jambu Mete di Kelurahan Benjala Kecamatan Bontobahari Kabupaten Bulukumba - Aditya, Shahrul; Amruddin, Amruddin; Rumallang, Ardi (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2024)
This study aims to determine the motivation of farmers in developing cashew farming in Benjala Village, Bontobahari District, Bulukumba Regency. The population of cashew farmers in Benjala Village, Bontobahari District, Bulukumba Regency is 58 cashew farmers. From this population, 15 cashew farmers were taken as a sample by means of deliberate sampling (simple purposive sampling). Based on research on farmer motivation in the Benjala Village area, it can be concluded that farmer motivation based on motivation theory can be concluded that it is not fulfilled properly. Based on the table from the research results in Benjala Sub-District, it shows that security needs get the highest score, namely 2.66 physical needs with a value of 2.30, appreciation needs with a value of 2.03, social needs with a value of 1.80, self-potential development needs get the lowest score, namely 1.36. This is due to many factors, starting from unstable prices, the long fertilization process, and the absence of government attention to cashew commodities and the absence of innovations or techniques that can be obtained by farmers, making farmers prefer to focus on corn and peanut commodities